2010
DOI: 10.1007/s11665-010-9683-4
|View full text |Cite
|
Sign up to set email alerts
|

A Fractional Factorial Design Study of Reciprocating Wear Behavior of Al-Si-SiCp Composites at Lubricated Contacts

Abstract: The lubricated reciprocating wear behavior of two composites A319/15%SiC p and A390/15%SiC p produced by the liquid metallurgy route was investigated by means of an indigenously developed reciprocating friction wear test rig using a fractional factorial-design approach. The main purpose was to study the influence of wear and friction test parameters such as applied load, sliding distance, reciprocating velocity, counter surface temperature and silicon content in composites, as well as their interactions on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The experiments were conducted according to the fractional factorial design (FFD). As Rajeev et al showed, the resolution of the design used was resolution V with five parameters . A model with interaction terms was chosen to fit the experimental data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The experiments were conducted according to the fractional factorial design (FFD). As Rajeev et al showed, the resolution of the design used was resolution V with five parameters . A model with interaction terms was chosen to fit the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…Resolution V designs are excellent because they reduce the number of runs and still obtain clean results. 13 To ensure the adequacy of the regression of the model obtained in this study, tests for the significance of individual model coefficients and tests for lack of fit should be performed. Analysis of variance (ANOVA) is usually applied to summarize the tests performed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wenlin et al [6] conducted experiments to study the effect of sliding speed on friction and wear performance of a copper-graphite composite and concluded that the coefficient of friction and wear rate of copper-graphite composites are largely dependent on sliding speed. Rajeev et al [7] studied the influence of wear and friction with respect to applied load, sliding distance, reciprocating velocity, counter surface temperature and silicon content in Al/SiC composites. Sai et al [8] studied the dry sliding wear behavior of copper fly ash composites using a pin on disc machine.…”
Section: Introductionmentioning
confidence: 99%